THE DIFFERENCE IN GRADE POINTS BETWEEN MORNING AND EVENING CHRONOTYPES AMONG PRECLINICAL MEDICAL STUDENTS - Cindy Leona Wangsa; Nawanto Agung Prastowo; Veronica Dwi Jani Juliawati; Francisca Tjhay (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Every person has a different diurnal preference, sleep-wake cycle, and alertness known as chronotype. There are three chronotypes, that is morning, evening, and intermediate type. Medical students with evening chronotype are still forced to follow the standard academic schedule in the morning, hence their sleep time is reduced. This problem results in lower grade points since sleep quality affects academic achievement. This study aimed to analyze the difference in grade points between morning and evening chronotypes among medical students.Methods: A comparative cross-sectional study was performed among 102 preclinical students class 2018 of School Medicine and Health Sciences of Atma Jaya Catholic University Indonesia. All personal data, grade points, and chronotypes were taken using google form. Chronotypes and sleep characteristics were determined with Munich ChronoType Questionnaire (MCTQ) by calculating weekend mid-sleep time and sleep debt. Unpaired t-test and binary logistic regression were used to analyze the statistical significance.Results: The results of evening chronotype 44.1% respondents, morning chronotype 31.4% respondents, and intermediate chronotype 24.5% respondents were obtained from 102 respondents. There were 65.7% of students with grade points greater than or equal to three and 34.4% lower than three. There was no significant difference in grade points between morning and evening chronotypes on semester 1, 2, 3, nor grade point average 3 (p>0.05). Conclusion: There is no significant difference in grade points between morning and evening chronotypes among preclinical students class 2018 of School Medicine and Health Sciences Atma Jaya Catholic University of Indonesia.